The trade-off between child labor and schooling: influence of social labeling NGOs in Nepal - Sayan Chakrabarty; Ulrike Grote; Guido Lüchters (University of Bonn, Center for Development Research (ZEF), 2006)
Does the labeling of products which have been produced without any child laborers contribute to increased welfare of children? This paper presents some results of a survey in Nepal conducted to analyze which factors determine the probability of a child to work, and to examine the influence of non governmental organizations (NGOs) which are engaged in social labeling, on the incidence of child labor and child schooling. Data were obtained from interviews with 410 households of Kathmandu Valley in Nepal. The results of the econometric analysis show that the probability of child labor (i) decreases if the carpet industry has implemented a labeling program, (ii) decreases if the adult's income increases ('luxury axiom'), (iii) decreases if the head of the household is educated, (iv) increases with the age of the head of the household, and (v) is increased in the presence of more children (aged 5-14) in the household. It can also be shown that labeling NGOs have a significant positive influence on sending the ex-child laborers to school. – – Erhöht die Kennzeichnung von Produkten, die ohne Kinderarbeit hergestellt werden, die Wohlfahrt von Kindern? Dieses Papier präsentiert Ergebnisse einer Befragung in Nepal, die durchgeführt wurde, um zu analysieren, welche Faktoren die Wahrscheinlichkeit bestimmen, dass ein Kind arbeitet. Darüber hinaus wird untersucht, welchen Einfluss Nichtregierungsorganisationen (NROs), die sich mit der Zertifizierung von Produkten nach sozialen Kriterien beschäftigen, auf das Vorkommen von Kinderarbeit bzw. auf die Schulausbildung haben. Dazu wurden 410 Haushalte im Kathmandu Valley in Nepal befragt. Es zeigt sich, dass die Wahrscheinlichkeit von Kinderarbeit (i) sinkt, wenn die Teppichindustrie ein soziales Kennzeichnungsprogramm implementiert hat, (ii) sinkt, wenn das Einkommen der Erwachsenen steigt ("Luxus-Axiom"), (iii) sinkt, wenn der Haushaltsvorstand über Bildung verfügt, (iv) zunimmt mit dem Alter des Haushaltsvorstandes und (v) zunimmt mit der Anzahl der Kinder (im Alter von 5-14) in einem Haushalt. Zudem kann gezeigt werden, dass NROs, die soziale Kennzeichnungsprogramme implementieren, einen signifikant positiven Einfluss auf die Schuleinweisung von ehemaligen Kinderarbeitern haben.
Keywords: 330